Thinkgame: cooperation to implement creative thinking and gamification for innovative online training of stem students - Meneses Benítez, Montserrat (2024)
This paper presents the collaborative experience that is under development as the European ERASMUS+ project THINKGAME (Cooperation to implement Creative Thinking and Gamification for innovative online training of STEM students). This project goal emerges from the need to enhance teachers' abilities to incorporate innovative methods in the e-learning systems. The ThinkGame initiative is taking profit of the teaching experience, pedagogical skills and technological competences from all project partners to develop a methodology and proof-of-concept for teachers seeking to create digital educational content that motivates students to develop their creative thinking skills. In this paper, the overall project setup will be presented both from the organisational point of view of the partnership and also presenting the collaborative approach for development and creation of digital educational content that motivates students to develop their creative thinking skills.